Successful Treatment of Antiepileptic Drug-Induced DRESS Syndrome with Pulse Methylprednisolone. (18th April 2013) - Kocaoglu, Celebi; Cilasun, Ceyda; Solak, Ece Selma; Kurtipek, Gulcan S.; Arslan, Sukru
Abstract : Drug reaction with eosinophilia and systemic symptoms (DRESS) syndrome is a rare but potentially life-threatening syndrome characterized by skin rash, fever, lymph node enlargement, and involvement of internal organs. It is most commonly induced by aromatic anticonvulsants and antibiotics. Nonaromatic anticonvulsants are rarely encountered as the causes of DRESS syndrome. In the present report, three discrete cases with DRESS syndrome developing due to three antiepileptic drugs, including valproic acid (nonaromatic), carbamazepine (aromatic), and lamotrigine (aromatic), and their treatment modalities were aimed to be discussed in light of the literature. To the best of our knowledge, our cases are the first children to be treated with pulse methylprednisolone in the literature.